2011
DOI: 10.3389/fpls.2011.00030
|View full text |Cite
|
Sign up to set email alerts
|

Potential Maternal Effects of Elevated Atmospheric CO2 on Development and Disease Severity in a Mediterranean Legume

Abstract: Global change can greatly affect plant populations both directly by influencing growing conditions and indirectly by maternal effects on development of offspring. More information is needed on transgenerational effects of global change on plants and their interactions with pathogens. The current study assessed potential maternal effects of atmospheric CO2 enrichment on performance and disease susceptibility of first-generation offspring of the Mediterranean legume Onobrychis crista-galli. Mother plants were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…A number of studies have indicated that genotypic (Wulff & Alexander, ; Curtis et al ., ; Ward & Strain, ; Andalo et al ., ; Bai et al ., ) and species‐specific (Farnsworth & Bazzaz, ; Jablonski et al ., ) differences interact with parental CO 2 concentrations to determine reproductive quality and/or outputs. The limited research also suggests that both female (Garbutt & Bazzaz, ; Jablonski et al ., ; Grünzweig, ) and male (Prasad et al ., ; Marshall et al ., ) components of reproductive fitness can be influenced by e CO 2 . However, the relative contribution of maternal vs paternal traits regulating seed germination responses to e CO 2 is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indicated that genotypic (Wulff & Alexander, ; Curtis et al ., ; Ward & Strain, ; Andalo et al ., ; Bai et al ., ) and species‐specific (Farnsworth & Bazzaz, ; Jablonski et al ., ) differences interact with parental CO 2 concentrations to determine reproductive quality and/or outputs. The limited research also suggests that both female (Garbutt & Bazzaz, ; Jablonski et al ., ; Grünzweig, ) and male (Prasad et al ., ; Marshall et al ., ) components of reproductive fitness can be influenced by e CO 2 . However, the relative contribution of maternal vs paternal traits regulating seed germination responses to e CO 2 is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, von Tiedemann and Firsching () found that nitrogen‐fixing legumes were more sensitive to elevated CO 2 and consequently to disease, while elevated CO 2 did not affect the leaf rust disease of wheat. Grünzweig () showed that high CO 2 could affect the susceptibility of Onobrychis crista‐galli to powdery mildew. In other cases, it has been shown that elevated CO 2 did not influence the disease of zucchini powdery mildew (Pugliese et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is impossible to achieve such a degree of control under natural field conditions. Over the last decade, phytotrons have been used to study the effects of CO 2 enrichment and temperature increases on infection rates for several pathosystems (Ainsworth and Long 2005;Chakraborty 2005;Garrett et al 2006;Gr€ unzweig 2011;Pugliese et al 2012a,b;Ferrocino et al 2013;Singh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Roots were extracted by gently washing soil from compartments with a rain‐spray nozzle over a 0.5 mm sieve. Data were not shown for Onobrychis crista‐galli because of infection by a pathogen during the course of the experiment (Grünzweig 2011).…”
Section: Methodsmentioning
confidence: 99%